The Availability and Safety Study of Remimazolam Besylate for Injection on Sedation of ERAS Patients Under Mechanical Ventilation in ICU: Protocol for a Randomized, Open-Label, Controlled Trial - Liu, Shengjun; Su, Longxiang; Zhang, Bo; He, Huaiwu; Li, Zunzhu; Li, Qi; Wang, Qianlin; Smith, Fang; Long, Yun (Frontiers in Medicine, 2021)
Introduction: The most common physiological and psychological disorders associated with critical care patients are pain and anxiety. Sedatives and analgesics are commonly used to relieve these symptoms. However, the adverse effects of sedatives and analgesics are common and inevitable. As a new type of sedative drug, limited number of trials are available to evaluate Remimazolam Besylate's availability and safety compared with propofol. Methods: This study is a single center, randomized, open-label, controlled trial. A total of 84 patients who meet ERAS criteria and receive mechanical ventilation in ICU, aged ≥18 years old will be included. Patients will be randomized (1:1) into two groups: Remimazolam Besylate group and Propofol group. The Primary outcomes includes satisfaction rate of sedation and incidence rate of major clinical events. Secondary outcomes including incidence of delirium, time to weaning and extubation, Difficulty of nursing RASS, BIS and PI, 28-days survival, side-effect and vital signs during medications, total dose and dose per kilogram body weight of analgesic and sedatives and incidence of rescue therapy in experimental group. Ethics and Dissemination: This trial has been approved by the ethics boards of Peking Union Medical College Hospital. Recruitment began in January 2022 and will continue until June 2022. Dissemination plans include presentations at scientific conferences, scientific publications, stakeholder engagement efforts and presentation to the public via lay media outlets. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT04947345